Making a "Pandhawa Lima" Puppet Puzzle Game Android based using Unity3D - Pamungkas, Addam Triatmadja (Jurnal Sistem Komputer, 2020)
As technology evolves, games become a media of entertainment that many people are interested in today. In addition to being entertainment, games can also be used as media broadening. Especially the insight of cultural heritage that is almost eliminated by the era and technological developments.Â  Wayang culture, children and adults are unfamiliar with the knowledge/stories about Wayang. Therefore, by utilizing the game as a medium that is easily accessible by various communities, in this research the author will design and build a game that brings together the cultural insight of Wayang, namely Wayang Pandhawa Lima. Combined with Puzzle genre games, users will be faced with fragments of puzzles that depict the figures of Wayang Pandhawa Lima. Where after completing the puzzle fragment that has been arranged, the user can read the information of the puppet that they have compiled. The creation of Wayang Pandhawa five puzzle game developed by Multimedia Development Life Cycle (MDLC) includes concept, design, material collection, manufacture, testing, and distribution. The creation process is done using the Unity 3D software that works on smart phone devices with the Android operating system. This application has been tested using Blackbox method as well as user testing with questionnaire method to 15 responodents. The result of this final task is that the application has been running according to the needs with a user interface value of 79.11% well categorized, usability aspect value of 84.67% well categorized and user experience aspect value of 84.44% well categorized.Â Keywords: Game; Android; Pandhawa Lima; MDLC; Unity3D